Governing through technology information artefacts and social practice - Kallinikos, Jannis (Technology, work and globalization, 2011)
Information produced and disseminated by an interlocking ecology of computer-based systems and artifacts currently provides the essential means for planning organizational operations and controlling organizational performances. This book describes the vital importance that digital information acquires in restructuring organizations